Engineering and application of glycosidase derived biocatalysts in the study of mycothiol pathway enzymes - Muneri, Ndivhuwo Olga (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhD)--Stellenbosch University, 2017.